2009
DOI: 10.1007/s11605-009-0898-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Outcomes in Living and Deceased Donor Liver Transplants for Primary Sclerosing Cholangitis

Abstract: Introduction Primary sclerosing cholangitits (PSC) is a progressive fibrosing cholangiopathy eventually leading to endstage liver disease (ESLD). While literature for deceased donor liver transplantation (DDLT) for PSC abounds, only a few reports describe live donor liver transplant (LDLT) in the setting of PSC. We present a single-center experience on survival outcomes and disease recurrence for LDLT and DDLT for ESLD secondary to PSC. Aim The aim of this study was to analyze survival outcomes and disease rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…This study confirms the findings of our previous study that superior graft quality as well as the favorable elective timing of LDLT conferred better patient and graft survival. 29 Also from this study, it appears that there has been an overall improvement in the 5-year survival for autoimmune and cholestatic diseases; however, it would be interesting to see the long-term outcome of these patients. …”
Section: Discussionmentioning
confidence: 71%
“…This study confirms the findings of our previous study that superior graft quality as well as the favorable elective timing of LDLT conferred better patient and graft survival. 29 Also from this study, it appears that there has been an overall improvement in the 5-year survival for autoimmune and cholestatic diseases; however, it would be interesting to see the long-term outcome of these patients. …”
Section: Discussionmentioning
confidence: 71%
“…However, the graft survival rate was significantly lower in patients undergoing LDLT. Kashyap et al [44] reported a higher recurrence rate of primary sclerosing cholangitis in patients undergoing LDLT. This difference may be due to the difference of aetiology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…42 Living-related liver transplant may be associated with an increased risk of developing recurrent primary sclerosing cholangitis, in support of the hypothesis that human leukocyte antigen mismatching may have a positive effect on disease recurrence. 43,44 Although living donor transplant may have advantages in timing and neoadjuvant protocols in patients who have cholangiocellular carcinoma, there may be an increased risk for developing recurrent primary sclerosing cholangitis. In contrast, mismatching may be associated with increased risk of graft rejection and allograft dysfunction, especially in patients who have liver transplant for other liver diseases, and this may outweigh the positive effects of mismatching on autoimmune mechanisms.…”
Section: Discussionmentioning
confidence: 99%